Developing Gloves As Media Used To Improve Students' Grammar Mastery - Alif Fataya; Muh Shofiyuddin (Universitas Veteran Bangun Nusantara, 2025)
This study presents Grammar Gloves, a useful tool that enables students to learn grammar, as manifested in better test results after their utilization in the experimental group. The aim is to develop this educational tool in four phases: Definition, Design, Development, and Deployment. Based on interviews, observations, and tests, data were gathered for the purpose of ensuring Grammar Gloves' suitability for students. Experts agreed that the tool is very suitable for being accurate and relevant. Media experts said it is easy for students to use and works well. Experts endorse the use of Grammar Gloves in schools. Additionally, during the media assessment, the control group exhibited an average score of 31. 31, while the experimental group recorded an average of 27. 17. In the post-test, the control group demonstrated an average score of 33. 83, whereas the experimental group achieved an average of 64. 42. The data indicates a notable improvement in grammar mastery among students who were instructed using the grammar gloves media. Consequently, it can be concluded that the development of grammar gloves media is both feasible and effective for teaching grammar.